Exposure to major coronary heart disease events reduces lung cancer risk: a mendelian randomization study based on a European population - Dongming He; Hongting Lu; Xinhuai Ou; Tiaozhan Zheng; Zhiwen Zheng; Zhanyu Xu; Xiaohong Duan; Shikang Li (BMC Cancer)
Abstract Objective This study seeks to elucidate the causal relationship between major coronary heart disease events (MCHDE) and lung cancer incidence through mendelian randomization (MR), with the goal of providing evidence to inform more effective lung cancer screening and prevention strategies. Methods Utilizing data from the IEU OpenGWAS project and FinnGen, this study employed a two-sample MR approach, with genetic variants serving as instrumental variables. Relevant single nucleotide polymorphisms (SNPs) associated with MCHDE and lung cancer were carefully selected, with particular attention given to mitigating potential confounders, such as smoking behaviors and statin use. Results The MR analysis, utilizing FinnGen's MCHDE as the exposure factor, revealed a significant reduction in the incidence of non-small cell lung cancer (NSCLC) [odds ratio (OR) 0.893, 95% confidence interval (CI) 0.800–0.998] and small cell lung cancer (SCLC) [OR 0.684, 95% CI 0.500–0.936], highlighting the protective effect of MCHDE against these cancer subtypes. However, this protective effect was not observed for other types of lung cancer. Furthermore, substituting FinnGen's MCHDE with that from IEU OpenGWAS did not yield similar protective effects across various lung cancer subtypes. Conclusions This study suggests that MCHDE reduce the risk of NSCLC in the U.K. population and SCLC in the Finnish population. However, given that the underlying mechanism through which MCHDE reduces the risk of NSCLC and SCLC remains unclear, it is premature to conclude that individuals exposed to MCHDE do not require lung cancer screening.